1976
DOI: 10.1017/s0022143000013770
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relationships in Sea Ice as a Function of Temperature

Abstract: ABSTRACT. Quantitative m eas ure m ents of the liquid water phase in a sa mple of sea ice w e r e m a de with a nucl ea r m a gn e ti c resonance sp ec tro met el'. The m ea sure ments a re used to co mpute the phase relationships in sea ice as a fun ction of tempe ra ture. A mod el for sea-wa ter based upon a mixture of seven binary sa lts is used for these computati ons. Th e n .m .1' . meas urem e nts a re related to th e so lva tion water wh ic h is associated with each bin a r y sa lt. This so lva tion wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 2 publications
4
59
2
Order By: Relevance
“…Although in the past sea‐salt aerosol around Antarctica has generally been assumed to have been produced by bubble bursting at the air sea interface (the dominant mode of production in lower latitudes), it is now believed that the major source of aerosol to the Antarctic atmosphere is concentrated brine expelled to the surface of newly‐forming sea ice, and the delicate ice crystals (frost flowers) that grow from this brine [ Wagenbach et al , 1998a; Rankin et al , 2002]. At low temperatures, salts begin to precipitate from the brine, with mirabilite (Na 2 SO 4 .10H 2 0) being lost below −8°C and sodium chloride fractionating below −23°C [ Richardson , 1976].…”
Section: Resultsmentioning
confidence: 99%
“…Although in the past sea‐salt aerosol around Antarctica has generally been assumed to have been produced by bubble bursting at the air sea interface (the dominant mode of production in lower latitudes), it is now believed that the major source of aerosol to the Antarctic atmosphere is concentrated brine expelled to the surface of newly‐forming sea ice, and the delicate ice crystals (frost flowers) that grow from this brine [ Wagenbach et al , 1998a; Rankin et al , 2002]. At low temperatures, salts begin to precipitate from the brine, with mirabilite (Na 2 SO 4 .10H 2 0) being lost below −8°C and sodium chloride fractionating below −23°C [ Richardson , 1976].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, based on a salinity-oxygen isotopic study, Yamamoto-Kawai et al ( 2009b ) concluded that the sea-ice melt component of surface water in the southern part of the Canada Basin has increased at a mean rate of 0.27 m/year in the top 50-m of the water column since 1987. Theoretically, the cold brine solution leads to chemical oversaturation and precipitation of CaCO 3 (Richardson 1976 ). Theoretically, the cold brine solution leads to chemical oversaturation and precipitation of CaCO 3 (Richardson 1976 ).…”
Section: Impact Of Seasonal Sea-ice Cyclementioning
confidence: 99%
“…However, this difference can also result from warmer temperatures at DDU (−15°C instead of −20°C at NM from May to October [ Konig‐Langlo et al , 1998]). Warmer temperatures can lead to either more frequent dilution by unfractionated frost flowers (present above −8°C) or less efficiency of the fractionation process since the sulfate to sodium ratio was found to decrease from 0.13 at −11°C to 0.07 at −14°C [ Richardson , 1976]. …”
Section: Winter Sea‐salt Fractionationmentioning
confidence: 99%